African Decolonial Theory : A Conversation - Daley, Patricia; Ndlovu-Gatsheni, Sabelo; Kimari, Wangui; Obeng-Odoom, Franklin; Tamale, Sylvia; Bauriedl, Sybille; Bawa, Sylvia; Carstensen-Egwuom, Inken; Adeniyi-Ogunyankin, Grace; Al-Bulushi, Yousuf; Ouma, Stefan (Antipode, 2026)
Antipode has become a key platform for engaging with decolonial and anticolonial scholarship, as well as adjacent fields such as Black geographies, Indigenous studies, Latin American feminism, and work on settler-colonialism. African reference points in this literature, however, have been far less common, both in the journal and more broadly in radical geography. Recognizing that there are several loci of enunciation for decolonial and anticolonial work, we committed to curating a series of conversations with and interventions by leading scholars from Africa and its diaspora associated with these epistemic and political projects. This long-read article, a first for the journal, brings these conversations and interventions together, highlighting the power of each as well as the common threads that connect them.
Keywords: decoloniality; Africa; commons; decolonial Marxism; Afro-feminism; deﬁant scholarship